Development of a Monoclonal Antibody Against Porcine CD163 SRCR5 Domain Which Partially Blocks Infection of PRRSV - Zhang, Yujiao; Zhang, Kuan; Zheng, Hao; Liu, Changlong; Jiang, Yifeng; Du, Nannan; Li, Liwei; Li, Guoxin; Yu, Lingxue; Zhou, Yanjun; Tong, Wu; Zhao, Kuan; et al. (Frontiers in Veterinary Science, 2020)
Porcine reproductive and respiratory syndrome virus (PRRSV), which seriously endangers the world pig industry, invades host cells through receptor-mediated endocytosis involving clathrin. CD163 is an essential receptor for PRRSV during its infection of cells. The scavenger receptor cysteine-rich 5 (SRCR5) domain of the CD163 molecule is necessary for PRRSV infection, and interacts with glycoproteins GP2a and GP4 of PRRSV, allowing the virus to infect the host cells. In this study, a monoclonal antibody (mAb) against the SRCR5-6 region of porcine CD163 was developed, and the target epitope of the mAb was determined as 497TWGTVCDSDF506, which is directly adjacent to the ligand-binding pocket (LBP) domain (487-495aa) of CD163. Further study indicated that the mAb could partially block PRRSV infection of its target cells, pulmonary alveolar macrophages. The mAb developed in the study may provide a foundation of antiviral therapy for PRRSV.